Efektivitas Pengawasan Limbah Perusahaan pada Dinas Lingkungan Hidup Kota Prabumulih - Hari Wahyudi; Mega Nugraha; Sunarto Sunarto (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2024)
Hari Wahyudi, English translation. This study aims to describe the effectiveness of the company's waste control at the Prabumulih City Environmental Service. This research was conducted for three months using a descriptive qualitative approach. Data was collected through interviews, observation, and documentation. Data analysis techniques were carried out by presenting data, reducing data, and drawing conclusions. The results showed that from the aspect of Organizational Characteristics, namely the form of supervision carried out by the Environmental Service through employees who worked in the field, it was approved and recommended by the Head of the Department of Environment. For specialized employees or field staff who carry out supervision, there must be a specialization to support better work abilities, as well as DLH employees in carrying out their duties, namely supervising companies that are directly related, more flexible and able to adapt, if this is indeed the case. not something urgent. For the Environmental Characteristic aspect, it is important for employees to adapt to the work environment, in this case, the Prabumulih City DLH employees must be able to adjust the conditions in the DLH office and also adapt to the conditions in the field in carrying out supervision in the hope that any decisions to be taken are right there. Aspects of Employee Characteristics, namely DLH employees in having good quality because they are in accordance with the educational qualifications and skills possessed, then also in carrying out employee duties ensuring that every company in Prabumulih City can progress but still ensuring the environment in the form of rivers, land and others does not damaged by pollution. As for the aspects of Management Policy and Practice, namely internal vertical and horizontal communication within the DLH Department, it is quite good, then communication with other institutions is also quite good. Then at the DLH Office, there are rarely awards given to employees, so it can be said that the reward system has not been able to stimulate employees to seek effective performance creation and performance and performance development.